Thromboinflammation as a Driver of Venous Thromboembolism - Gauchel, Nadine; Krauel, Krystin; Hamad, Muataz Ali; Bode, Christoph; Duerschmied, Daniel (Hämostaseologie, 2021)
Thrombus formation has been identified as an integral part in innate immunity, termed immunothrombosis. Activation of host defense systems is known to result in a procoagulant environment. In this system, cellular players as well as soluble mediators interact with each other and their dysregulation can lead to the pathological process of thromboinflammation. These mechanisms have been under intensified investigation during the COVID-19 pandemic. In this review, we focus on the underlying mechanisms leading to thromboinflammation as one trigger of venous thromboembolism.
Keywords: thromboinflammation; immunothrombosis; innate immunity; venous thromboembolism; COVID-19